2022
DOI: 10.1007/s00535-022-01862-y
|View full text |Cite
|
Sign up to set email alerts
|

A review on the current status and definitions of activity indices in inflammatory bowel disease: how to use indices for precise evaluation

Abstract: Many clinical trials have been conducted for inflammatory bowel disease (IBD), so various clinical indices (CIs) and endoscopic indices (EIs) have also been evaluated. However, recently, with the progress of IBD management, review of established indices from previous studies, and establishment of new indices, the landscape of the use of indices in clinical trials have changed. We investigated the number and frequency of the indices adapted in recent clinical trials for ulcerative colitis (CI and EI) and Crohn’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 147 publications
0
32
0
Order By: Relevance
“…Previous studies of evaluating endoscopic disease activity in UC have mainly focused on clinical scoring, biochemical measures, or building multi-index prediction models ( 10 , 12 , 45 ). However, the clinical scoring methods, such as the Seo Index and simple clinical colitis activity index correlate poorly with endoscopic disease activity ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of evaluating endoscopic disease activity in UC have mainly focused on clinical scoring, biochemical measures, or building multi-index prediction models ( 10 , 12 , 45 ). However, the clinical scoring methods, such as the Seo Index and simple clinical colitis activity index correlate poorly with endoscopic disease activity ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-endoscopic disease activity indices, such as the Seo Index and simple clinical colitis activity index, can also quantify the severity of the disease and predict prognosis clinically ( 10 , 11 ). However, non-endoscopic disease activity indices fail to correlate well with endoscopically proven intestinal inflammation ( 10 , 12 ). Moreover, some clinical scales in disease activity scoring systems include a degree of subjectivity, so the results can be biased.…”
Section: Introductionmentioning
confidence: 99%
“…A CDAI score of < 150 is used to define remission [ 5 , 53 ]. A recent literature survey in Japan found that the CDAI was the most commonly used index in clinical trials [ 54 ]. However, the threshold for treatment escalation based on CDAI score differs between studies.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…While the CDAI is widely used in a clinical research context, it may not be practical for use in clinical practice, because it is complicated to calculate, varies between patients (especially in relation to items such as abdominal pain) and relies on patients completing symptom diaries, uses a poorly defined standard for body weight, does not accurately assess the severity of fistulas and stenosis, and is weighted heavily toward diarrheal symptoms [ 1 , 54 ]. The simpler Harvey–Bradshaw index (HBI) may be a more suitable tool for the assessment of disease activity in clinical practice (Supplementary Table 6), but this is also weighted by diarrhea meaning that CD patients with an increased stool frequency are likely to show a score disproportionate to disease activity [ 1 , 54 ]. Studies using the HBI generally define lack of response as a score of ≥ 5 [ 28 , 42 ], although some have used a score of > 4 [ 60 , 61 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…The score is convenient, straightforward, and quick to use, however, it performs poorly in terms of accurately portraying the disease activity. In the original publication, the proportions of complete responses, partial responses, and no responses in each administration group were compared with those in the placebo group to assess efficacy 4. In the landmark OCTAVE study, the definition used as follow: (a) clinical response: reduction of ≥3 points on the Mayo scale and a relative decrease from baseline of 30% or more with an accompanying decrease in the rectal bleeding subscore of 1 point or more or an absolute rectal bleeding subscore of 0 or 1; (b) clinical remission: defined as a Mayo score ≤2, with no subscore >1; (c) endoscopic response: defined as a decrease from baseline in the endoscopy subscore by at least 1; (d) endoscopic remission: endoscopic subscore of 0 5.…”
mentioning
confidence: 99%